Agricultural Research Priority Setting: Information Investments for the Improved Use of Research Resources - Mills, Bradford F. (International Service for National Agricultural Research, 1998)
Managers face a number of practical issues in designing procedures for agricultural research priority setting: Who will set priorities? What skills or tools do they need? Similarly, socioeconomists and others who implement priority-setting processes need concrete advice on how to undertake each step. This book addresses issues of process design and implementation. It leads readers through the major steps and questions involved in setting program-level priorities in agricultural research organizations. Examples from the Kenya Agricultural Research Institute (KARI) illustrate applications of the methods and issues discussed.